Genetic factors affecting the composition and quality of cow's milk - Poulsen, Nina Aagaard (Burleigh Dodds Series in Agricultural Science, 2021)
This chapter reviews the genetic factors affecting the composition and quality of cow's milk. It starts by discussing how different breeds of cattle can affect the composition of milk. The chapter then goes on to examine milk proteins, genetic variants and post-translational modifications. It then discusses milk coagulation and other functional properties, before highlighting the genetic influence of fatty acids on minor milk components. The chapter also discusses using mid-infrared spectroscopy for genetic parameter estimation, before concluding with a section on the possibilities for genetic improvement in relation to dairy milk.